Development of vortex detection algorithm for fluid dynamics data - Nasruddin A'aidil Shari (2016)
Vortices can cause many problems in the many engineering products such as cars and airplanes. In this paper, we go through a simple and efficient algorithm made by Ming Jiang and others (2002) [4] to detect vortices. We made use of his idea of Sperner’s Lemma as a basis for the algorithm to detect and visualize vortices in both 2d and 3d using a 3-label scheme and 4-label scheme. We also extend the use of the algorithm to visualize (volumetrically) detailed characteristics of vortices such as size, shape and hollowness by combining results of different accuracy constants. The algorithm proved to be efficient and accurate in detecting vortices with 3-labels scheme and 4-labels scheme having their own benefits and drawbacks. Combining the results of different accuracy results was also successful in displaying different characteristics of a vortex.